Challenging the conceptual framework of maintenance hosts for influenza A viruses in wild birds. Issue 3 (20th December 2016) - Caron, Alexandre; Cappelle, Julien; Gaidet, Nicolas
Summary: The conceptual framework considering Anseriformes and Charadriiformes as the main maintenance hosts for influenza A viruses (IAV) in wild birds has shaped IAV research and surveillance over the last decades. We challenge this framework by reviewing the world‐wide surveillance data on non‐Anseriformes and non‐Charadriiformes (NANC) species, generally considered as playing little role in IAV maintenance, available in literature and online data bases (close to 200 sources). Globally, we found an IAV infection rate of 1·51% (95% CI, 1·44–1·59%) for c. 101 000 birds tested from NANC species. If Anseriformes have, as expected, a higher infection rate than any other bird orders, eight bird orders have an infection rate higher or close to the Charadriiformes infection rate, challenging the status of Charadriiformes. We interpret the attention paid in favour of Charadriiformes by an extrapolation bias from data collected in hotspots of IAV infection in Charadriiformes (e.g. Delaware Bay, USA). The growing data on IAV in wild birds world‐wide, summarised here, support two non‐exclusive hypotheses: (i) the quality of the diagnostic tools and techniques used explain the patterns observed; (ii) IAV maintenance is determined by complex multi‐host systems composed of multiple bird species, dependent on the ecosystem and its bird diversity and composition. Synthesis and applications . Our results have two main implications. First, new research and surveillance should be designed in order to understand influenza A viruses ecology in wild birds across the world, along with appropriate diagnostic tools and new hypotheses and dedicated protocols. This should be done in line with our new conceptual framework that conveys less a priori than its predecessor. Second, our results call for more bridging between biological and epidemiological sciences in order to tackle disease ecology in multi‐host systems. Abstract : Our results have two main implications. First, new research and surveillance should be designed in order to understand influenza A viruses ecology in wild birds across the world, along with appropriate diagnostic tools and new hypotheses and dedicated protocols. This should be done in line with our new conceptual framework that conveys less a priori than its predecessor. Second, our results call for more bridging between biological and epidemiological sciences in order to tackle disease ecology in multi‐host systems.